Pengaruh Konten Edukasi Karir Vina Muliana dalam Media Sosial Tiktok Terhadap Orientasi Karir Generasi Z dengan Perilaku Fomo Sebagai Pemediasl - Estri Nastiti; Waskito, Jati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the impact of career education content from Vina Muliana on the TikTok social media platform on the career orientation of Generation Z, with the Fear of Missing Out (FoMO) behavior serving as a mediating variable. The study employs a quantitative method with purposive sampling and involves 150 Generation Z respondents who are active TikTok users and follow Vina Muliana's account. The results indicate that career education content has a positive and significant impact on FoMO behavior, which in turn influences Generation Z's career orientation. Additionally, FoMO behavior significantly mediates the relationship between career education content and career orientation. This study concludes that TikTok, as a social media platform, plays an important role in shaping the career orientation of Generation Z, and that FoMO behavior can act as a trigger for career exploration.